Analisis Eksternal Sebagai Upaya Pengembangan Bisnis Perdagangan Internasional Baru (Studi Kasus: PT. GFA) - Sabilla, Dipty Maura (Jurusan Akuntansi Politeknik Negeri Padang, 2023)
Indonesia is known as an agricultural country with abundant natural wealth and the majority of its population work as farmers. Agricultural products in Indonesia are in excess supply, while market demand for agricultural products abroad is very large. PT. GFA is a company that exports agricultural products from local farmers and SMEs which exports on HS07 and HS09. From this research it was found that the government has a very large role in the export business, for example through international agreements. From economic factors, there was an increase in vegetable exports but a decrease in coffee exports. From a socio-cultural perspective, PT. GFA can be sourced from local farmers. The existence of technological factors makes it easier for PT. GFA in marketing and control. Furthermore, PT. GFA has moderate buyer bargaining power, as evidenced by the Indonesian market penetration of trade value in Asia. However, the bargaining power of suppliers at PT. GFA is high, this is because the company does not have the goods but takes them from suppliers. On the other hand, the threat of small substance products is because HS07 and HS09 are commodities that cannot be replaced. Lastly, PT.GFA has a low threat of new entrants because to become an exporter requires quite a large amount of capital.